دوافع التحرش الجنسي في الوسط الجامعي من وجهة نظر الطلبة الجامعيين - غربي, جهينة (جامعة الوادي university of Eloued, 2022)
الملخص: هدفت الدراسة الحالية إلى التعرف على دوافع التحرش الجنسي في الوسط الجامعي من وجهة نظر طلبة الجامعة، حيث تم صياغة التساؤل الرئيسي للدراسة، ما دوافع التحرش الجنسي في الوسط الجامعي من وجهة نظر طلبة الجامعة؟ وتم الاعتماد في الدراسة على المنهج الوصفي الاستكشافي لملائمته للدراسة الحالية، حيث تم تطبيق مقياس دوافع التحرش الجنسي المعد من طرف الباحثة على عينة قوامها 120 طالب وطالبة مقسمين إلى (60) طالب و(60) طالبة، وبعد تطبيق أدوات الدراسة تم استخدام التكرارات والنسب المئوية للإجابة على تساؤلات الدراسة، حيث توصلت الدراسة إلى النتائج التالية: - توجد دوافع داخلية للتحرش الجنسي في الوسط الجامعي من وجهة نظر طلبة الجامعة. - توجد دوافع خارجية للتحرش الجنسي في الوسط الجامعي من وجهة نظر طلبة الجامعة. Abstract : The current study aimed to identify the motives behind sexual harassment in university campus according to the point of view of university students where the main query of the study was formulated as follows: what are the motives behind sexual harassment in university campus according to the point of view of university students? The study relied on the exploratory descriptive approach for its relevance to the current study. However, the scale of sexual harassment motives prepared by the researcher was applied to a sample of 120 students divided into )60)maile and (60) female students. After applying the study tools، iterations and percentages were used to answer the study questions which results to the following: • There are internal motives behind sexual harassment in university campus according to students’ point of view. •There are external motives behind sexual harassment in university campus according to students’ point of view.
دراسة ميدانية بكلية العلوم الاجتماعية بجامعة-الوادي
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: التحرش الجنسي، التعليم العالي والجامعة; Harcèlement sexuel, enseignement supérieur et université; Sexual harassment, higher education and the university